Mapping Individual, Relational, and Contextual Factors onto Posttraumatic Stress Symptoms and Resilience - Thomsen, Kari N. (Journal of interpersonal violence, 2023)
Posttraumatic stress symptoms (PTSS) and resilience are two well-established outcomes following trauma exposure, but little work has examined the unique associations between these outcomes and factors across the social ecology. This theoretically grounded study assessed how individual, relational, and contextual social ecological factors relate to PTSS and resilience. Participants included 606 college students (18–25 years, Mage = 20.79, SD = 1.86; 82.51% Female; 56.60% White, 29.37% Black or African American, 5.78% Asian, 8.25% Other races) with exposure to at least one traumatic event. Two hierarchical linear regression models examined associations between individual (i.e., emotion dysregulation, anger severity), relational (i.e., family support, friend support), and contextual (i.e., community cohesion, community disorder) factors, and PTSS and resilience. At the individual level, higher emotion dysregulation was associated with higher PTSS and lower resilience; anger severity was not related to either outcome. At the relational level, more friend support was negatively associated with PTSS. Friend and family support were positively related to resilience. At the contextual level, community cohesion was positively associated with resilience, but not PTSS, and community disorder was unrelated to both outcomes. Findings demonstrate unique factors across the social ecology that differentially relate to PTSS and resilience. Variables at all three ecological levels were associated with resilience, whereas only individual and relational variables were related to PTSS. Replication with longitudinal data could inform treatments for trauma-exposed individuals that may mitigate PTSS and bolster resilience.